2018
DOI: 10.1186/s13104-018-3514-3
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the 2016 dengue outbreak in Nepal

Abstract: ObjectiveThe objective of this study was to obtain clinical, virological and demographic data detailing the 2016 dengue outbreak in Nepal.ResultsDengue disease was first reported in Nepal in 2004 and several major outbreaks have occurred since then, with a significant impact on public health. An outbreak of dengue fever occurred in Nepal during June to November 2016, with a peak number of cases reported in September. 1473 patients with laboratory confirmed DENV infections visited or were admitted to hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 27 publications
5
33
0
Order By: Relevance
“…5 Khetan, Stein, Chaudhary, Rauniyar, Upadhyay, Gupta, et al first reported dengue fever in Nepal in 2004, which was followed by several major outbreaks. 6 Huy et al reported 2922 patients in Vietnam in 2017. 7 An unprecedented number of cases of dengue/dengue haemorrhagic fever were reported in Delhi from August to November 1996 with many deaths.…”
Section: Discussionmentioning
confidence: 99%
“…5 Khetan, Stein, Chaudhary, Rauniyar, Upadhyay, Gupta, et al first reported dengue fever in Nepal in 2004, which was followed by several major outbreaks. 6 Huy et al reported 2922 patients in Vietnam in 2017. 7 An unprecedented number of cases of dengue/dengue haemorrhagic fever were reported in Delhi from August to November 1996 with many deaths.…”
Section: Discussionmentioning
confidence: 99%
“…The major clinical symptoms of dengue infection in Nepalese patient reported by Khetan et al were fever (100%), cerebral pain (71.3%), rashes (11.3%), retro-orbital torment (23.5%), retching (23.4%), joint pain (32.1%), and thrombocytopenia (85.7%) [8]. During the first decade (2004-2013) of Nepalese dengue history, two major epidemics in 2010 and 2013 have been recorded [9].…”
Section: Dear Editormentioning
confidence: 95%
“…Sparse information on DENV infection in Nepal was available prior to 2004 [ 17 ], which changed with the report of one Japanese foreigner being diagnosed with dengue fever in 2004 [ 18 ]. Since then, four DENV outbreaks occurred in Nepal, with the first endogenous dengue outbreak in the Chitwan district dating to 2006 [ 19 ]. At that time, the circulation of all four DENV serotypes was found in nine districts of the low-land Terai region [ 20 ].…”
Section: Methodsmentioning
confidence: 99%